Entre linhas: : os diálogos interartísticos entre Amarelo-Vermelho-Azul, de Wassily Kandinsky e Cami-nho das Águas, de Piatan Lube - Silva, Douglas Gomes (Revista do Colóquio, 2020)
This article discusses the interartist dialogues between Wassily Kandisnsky Yellow-Red-Blue painting (1925) and Piatan Lube urban intervention Water Way (2008). At the level of providing understanding on the theme presented and weaving the links between the works, the work will be brought together by studies by Giulio Carlo Argan (2005), Nelson Brissac Peixoto (2012) and Alexandre Siqueira de Freitas (2012), seeking to create respectively a poetic reading of what the field of art understands about city, urban intervention and resonances. In this sense, of an essayistic nature, it seeks to create through intracodes new tools for analysis and reading of the works.